1998
DOI: 10.1677/erc.0.0050059
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of 50 patients with malignant abdominal paragangliomas and malignant pheochromocytomas

Abstract: Background: Tumors of the paraganglionic system represent a distinct, albeit uncommon, clinical entity characterized by catecholamine hypersecretion and hemodynamic instability; initial pathologic examination often cannot predict benign vs malignant behavior. An analysis of the clinical outcome of patients with known malignant tumors may serve to enhance the initial evaluation and therapeutic plan of all patients presenting with pheochromocytoma or paraganglioma. Results: Among the 30 patients with paraganglio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Other studies have shown 5-year survival of between 30% and 80% (Sclafani et al , 1990; Vassilopoulou-Sellin, 1998). Sclafani et al (1990) reported a 5-year survival of 36%.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Other studies have shown 5-year survival of between 30% and 80% (Sclafani et al , 1990; Vassilopoulou-Sellin, 1998). Sclafani et al (1990) reported a 5-year survival of 36%.…”
Section: Discussionmentioning
confidence: 93%
“…Sclafani et al (1990) reported a 5-year survival of 36%. Vassilopoulou-Sellin's (1998) study had a very long follow-up of 50 patients and showed a 5-year survival of paragangliomas of 30% and phaeochromocytoma of 80%. The advances in the genetics of CCTs being identified may explain the difference between Sclafani's study and ours, with patients identified much earlier and treated, hence showing a better survival.…”
Section: Discussionmentioning
confidence: 99%
“…There are no reliable morphologic criteria to differentiate microscopically benign from malignant paraganglioma. Its malignant potential is defined after a metastatic lesion or direct invasion is found in a site with no residual embryonic paraganglionic tissue [3,4].…”
mentioning
confidence: 99%
“…The sample size and follow‐up after OLT have been limited in these series [5,6]. The Hannover group published their results in 12 patients who underwent OLT for metastases from NET [4]. They had one operative mortality and two patients developed recurrent disease and died secondary to their malignancy.…”
mentioning
confidence: 99%